A case of renal cell carcinoma metastases to the neck after long-term latency in the setting of chronic lymphocytic leukemia progression - Zabrocka, Ewa; Sierko, Ewa; Wojtukiewicz, Marek Z. (European Journal of Oncology and Environmental Health, 2017)
We report on a 71-year-old man with a three-year history of chronic lymphocytic leukemia (CLL) who underwent left-sided nephrectomy due to renal cell carcinoma (RCC) 16 years earlier. Because of the CLL progression, he was being treated with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone) regimen, when he started to complain of hoarseness and cough. Laryngological examination disclosed tumorous lesion involving right half of the larynx. On computed tomography (CT) scans numerous lesions in the neck region (e.g. larynx, thyroid gland) were revealed. RCC metastases were confirmed in the histopathological examination of the specimen from the larynx. Since the treatment with interferon alpha was intolerable, eight courses of multi-kinase inhibitor, sorafenib, were applied. Despite the initial regression, progressive disease was shown in post-treatment CT. At present, the patient is being treated with m-TOR inhibitor, everolimus.